Value of 18F-fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) in assessment of response to preoperative chemotherapy in pediatric sarcoma - Ahmed Mohamed Rashad; Ahmed Mohamed Abougabal; Shady Hassan Fadel; Walid Mohamed Omar; Khaled Mohamed Moghazy (The Egyptian Journal of Radiology and Nuclear Medicine, 2019)
Abstract Background The aim of this retrospective study was to highlight the role of FDG PET/CT in the assessment of tumor response to preoperative chemotherapy in pediatric sarcoma. Eighteen patients were included in our study: 13 patients were males and 5 were females ranging between 1 and 18 years with a mean age of 13.3 years. The patients had pathologically proven osseous or soft tissue sarcoma. All patients underwent sequential 18F-FDG PET/CT before (PET-CT1) and after (PET-CT2) neoadjuvant chemotherapy. Maximum standardized uptake value (SUVmax) was measured in the primary lesion on PET/CT1 (SUV1) and PET/CT2 (SUV2). After surgery, the effects of neoadjuvant chemotherapy were evaluated histopathologically: ≥ 90% necrosis indicated was considered a good response and < 90% necrosis was considered a poor response. The correlation between SUV2 and the histologic response was assessed. Results The sensitivity, specificity, positive predictive value, and negative predictive value of SUV2 for assessment of treatment response were 100%, 91.67%, 85.71%, and 100%, respectively. The overall accuracy was found to be 98.3%. Conclusions 18F-FDG PET/CT provides a reliable non-invasive diagnostic tool in assessment of response to preoperative chemotherapy in pediatric sarcoma.